The determination of sediment acceration rate using 210Pb in Johore Coastal Water, Malaysia - Yunus, Kamaruzzaman; Mohamad Shazili, Noor Azhar; H.A.G, Norhizam; K.Y.S., Willison (Universiti Putra Malaysia Press, 2010)
Ocean sediments give information on the paleoclimatic evolution in the geological past which gives detailed information on both the age of the sediments and both paleoceanographic and paleoclimatic conditions during sedimentation. One possible way to date sediments is with 210Pb method which can be used to date sediments up to 100 years. In this study, two core samples labelled as JB15 and JB17 were collected using pledging corer, analysed and measured for the activity of 209Po and 210Po using the alpha spectrometer. Applying the methods, average sedimentation rates for JB15 and JB17 were calculated as 0.38 cmyr-1 and 0.43 cmyr-1, respectively. Assuming that the sedimentation rate values are accurate, this might imply that the sediments at the depth of 30 cm were deposited 70 years ago.